Validation of a predictive tool for the heading of turret-moored vessels. (1st December 2016) - Milne, I.A.; Delaux, S.; McComb, P.
Abstract: This paper presents the validation of tool which combines a model of the steady wind, current and wave loads with numerical estimates of the metocean conditions to predict the heading of a turret-moored vessel such as an FPSO. Estimates of the wave-induced mean drift contribution were obtained using an open-source three-dimensional boundary element code. Empirical data from reduced-scale tests were used to obtain the wind and current loads, which were shown to enable more reliable estimates than would be possible using data for very large crude carriers. The environmental conditions were predicted numerically using multi-resolution nested models which assimilate observed data. Using measurements from an operating FPSO for full-scale validation, the model was shown to be able to predict the heading for a range of environmental conditions including non-collinear seas, swells and winds to an accuracy typically within 5%. Preliminary estimates of the vessel roll amplitudes also agreed favourably with measured values. It is envisaged that the model will be attractive for operators of FPSOs in better facilitating the identification of dangerous conditions. This could ultimately lead to safer and more efficient operations. Abstract : Highlights: Heading predictions were validated using full-scale data from an operating FPSO. Reliable predictions for complex seas including those with multiple possible equilibria. Wind and current load coefficients for VLCCs found to be unreliable for FPSOs.